Crow smarts : inside the brain of the world's brightest bird - Turner, Pamela S. (Scientists in the field., 2016)
Presents information about crows, recently recognized as intelligent and able to use tools and solve problems. Introduces several crows living on a Pacific island who are learning and adapting in surprising ways.